Project management - Lock, Dennis (Farnborough : Gower Press, 1977)
The first edition of Project management was written with this problems in mind. Clearly there was need for a need for a new approach to this subject: a book embracing all aspects of project management rather than yet another work devoted solely to one particular technique, treated in isolation. Another objective was to write the book for those actually engaged in the planning and control of industrial projects as far as possible avoiding jargon and unnecessary mathematics.
Includes index.
Includes bibliographical references and index.
hza 20/07/2018
Loans
Keywords: Project management